Filosofi Sitou Timou Tumou Tou Merawat Manusia Dalam Bingkai Moderasi Beragama - Anita Inggrith Tuela; Yolanda Nani Palar; Heliyanti Kalintabu (Vox Dei: Jurnal Teologi dan Pastoral, 2023)
Sitou Timou Tumou Tou is a philosophy that lives in the life of the Minahasa people. This philosophy has existed for a long time and this philosophy was initiated by Gerungan Saul Samuel Jacob Ratulangi, with the intention that the Minahasa people uphold to love and love fellow humans. However, over time, the meaning of this philosophy began to shift from Minahasa society. This shift can be seen in several situations, where there is bullying between religions, different cultures, and even the same religion and culture, brawls between villages that cause casualties. This study aims to examine the meaning of the philosophy of Sitou Timou Tumou Tou, furthermore, connect the meaning of the philosophy with Christian values and integrate these values with the principles of religious moderation, and socialize this paper to one of the intended villages in Bolaang Mongondow North Sulawesi, then carry out a Group Discussion Forum in the village. To achieve this research goal, it is necessary to use appropriate research methods. The research method used is qualitative research method with a literature study approach and using the FGD method. The results of this study show that the human values contained in the philosophy of Sitou Timou Tumou Tou are in line with the human values contained in religious moderation. The philosophy of Sitou Timou Tumou Tou is rooted in Christian values contained in the Bible regarding the teaching of love for fellow humans.